2016
DOI: 10.1016/j.tifs.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Food-derived dipeptidyl-peptidase IV inhibitors as a potential approach for glycemic regulation – Current knowledge and future research considerations

Abstract: Background: Diabetes, which currently affects 1 in 11 adults, is considered one of the biggest worldwide health crises of the 21 st century. Over the last decade, synthetic inhibitors of the enzyme dipeptidyl-peptidase IV (DPP-IV) have emerged as an effective pharmaceutical approach for the management of type 2 diabetes. These molecules exert their beneficial effect by preventing the inactivation of gut-derived hormones that play a pivotal role in glycemic regulation. More recently, food components have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 96 publications
3
109
0
Order By: Relevance
“…Currently, extensive efforts have been put toward the development of food‐derived peptides enabling to inhibit the activity of DPP‐IV, which may lead to type 2 diabetes for its antagonism ability against the incretin hormones glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) (Lacroix & Li‐Chan, ; Nongonierma & FitzGerald, ). DPP‐IV inhibitory peptide has been developed as a potential approach in the therapy of type 2 diabetes, and a considerable amount of studies have revealed that plentiful food protein‐derived peptides shown potent DPP‐IV inhibitory activity, including plant‐derived peptides such as casein, rice, and soy as well as animal‐derived peptides such as milk and pork (Huang, Hung, Jao, Tung, & Hsu, ; Nongonierma & FitzGerald, , ).…”
Section: Biological Activities and Corresponding Mechanisms Of Bioactmentioning
confidence: 99%
“…Currently, extensive efforts have been put toward the development of food‐derived peptides enabling to inhibit the activity of DPP‐IV, which may lead to type 2 diabetes for its antagonism ability against the incretin hormones glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) (Lacroix & Li‐Chan, ; Nongonierma & FitzGerald, ). DPP‐IV inhibitory peptide has been developed as a potential approach in the therapy of type 2 diabetes, and a considerable amount of studies have revealed that plentiful food protein‐derived peptides shown potent DPP‐IV inhibitory activity, including plant‐derived peptides such as casein, rice, and soy as well as animal‐derived peptides such as milk and pork (Huang, Hung, Jao, Tung, & Hsu, ; Nongonierma & FitzGerald, , ).…”
Section: Biological Activities and Corresponding Mechanisms Of Bioactmentioning
confidence: 99%
“…Two of the peptides (Ala-Trp and Val-Trp) were inactive towards renin, while the renin inhibitory activity determined experimentally was lower or of the same order as the predicted inhibition for Leu-Trp and Ile-Trp, respectively. 53 In addition, Ile-Trp (IC 50 ¼ 2.3 AE 0.07 mM) was a newly identied renin inhibitory peptide also displaying high ACE inhibitory activity (IC 50 ¼ 4.74 AE 0.04 mM). Interestingly, Ile-Trp had previously been shown to induce a signicant reduction in SBP in SHR studies.…”
Section: Renin Inhibitory Peptidesmentioning
confidence: 99%
“…Inhibiting DPP-IV activity leads to an increase of insulin secretion and therefore a decrease in blood glucose level in vivo (Mochida, Hira, & Hara, 2010;Ishikawa et al, 2015). DPP-IV (also known as DPP-4 or cluster of differentiation 26) is a soluble or membrane-anchored enzyme that degrades incretin hormones, glucagon-like peptide (GLP)-1 and glucose-dependent insulinotropic polypeptide, inactivating more than 95% of the GLP-1 produced in the body (Lacroix & Li-Chan, 2016). DPP-IV (also known as DPP-4 or cluster of differentiation 26) is a soluble or membrane-anchored enzyme that degrades incretin hormones, glucagon-like peptide (GLP)-1 and glucose-dependent insulinotropic polypeptide, inactivating more than 95% of the GLP-1 produced in the body (Lacroix & Li-Chan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Food-derived peptides have low biostability due to their scissile peptide bonds (Udenigwe & Fogliano, 2017), and their bioavailability is reported to be in amounts as low as pico-and nanomolar concentrations (Xu, Hong, Wu, & Yan, 2019). Moreover, inhibitory effect of food peptides is lower than that of rationally designed synthetic gliptins (Lacroix & Li-Chan, 2016). Nonetheless, food protein-derived peptides are promising as functional ingredients for managing T2D and as natural adjuvant to support the effect and reduce the use of synthetic DPP-IV inhibiting drugs.…”
Section: Introductionmentioning
confidence: 99%